ПІДВИЩЕННЯ ЕНЕРГОЕФЕКТИВНОСТІ БРАГОРЕКТИФІКАЦІЙНИХ УСТАНОВОК І СТУПЕНЮ ОЧИСТКИ БІОЕТАНОЛУ - Bulii, Yu.V.; Obodovych, O. M. (Institute of Engineering Thermophysics of NAS of Ukraine, 2018)
The aim of the work was a study the energy efficiency of the heads and fusels concentrating column and beer still, the degree of purification of ethanol in the process of the separation of light fraction and the efficiency of the process of а beer distillation by increasing residence time of the liquid on the trays for contact with the vapor. The technology of rectification with controlled cycles of fluid retention on the stages of the contact and its overflow without mixing to the adjacent trays is proposed. For implementing the method the experimental column was equipped with scaly trays with coaxial arrangement of scales, which excluded the linearity of the fluid motion. The overflow holes of each tray is alternately opened and closed by movable valves associated with the driving mechanism in accordance with the controller program. Change the cross-section of the trays at 45-50 % resulted in an immediate reduction of rate of vapor and provided the spilled liquid through the overflow hole and the gap of scales. Due to this time the overflow was reduced from 5 to 2 seconds. It was studied that the increasing of the residence time of the beer on the trays to 12 seconds can increase the concentration of alcohol in beer distillate by 28 % in comparison with the standard columns. The coaxial arrangement of scales eliminates the possibility of formation of stagnant zones and burning of suspended particles of a beer. Specific consumption of heating steam to the process distillation not exceed 16 kg/dl of absolute alcohol of a beer. In the process of the separation of light fractions with the fluid retention on trays to 20 seсonds a degree of extraction of aldehydes, higher alcohols of fusel oils and methyl alcohol grew on average by 30 %, the multiplicity of concentration of light and intermediate impurities increased by 32 %. The consumption of heating steam for the distillation process was reduced to 14 kg/dl of absolute alcohol. To increase the efficiency of contact devices, it is advisable to prolong the residence time of the liquid on the trays until close to the equilibrium state of phases, and to provide overflow of liquid without mixing to the adjacent trays, to use trays with full compensation of co-current and alternating cross-section.